2020
DOI: 10.3390/met10070921
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Static Compression Deformation and Energy Absorption Characteristics of Basalt Fiber-Containing Closed-Cell Aluminum Foam

Abstract: In this work, closed-cell aluminum foams with 4 wt.% contents of short-cut basalt fibers (BFs) were successful prepared by using the modified melt-foaming method. The pore size of BF-containing aluminum foam and commercially pure aluminum foam was counted. The distribution of BF and its effect on the compressive properties of closed-cell aluminum foams were investigated. The results showed that the pore size of BF-containing aluminum foams was more uniform and smaller. BF mainly existed in three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To evaluate the energy absorption performance of the aluminum foam, they also proposed the energy absorption efficiency and the ideal energy absorption efficiency. The energy absorption efficiency is broadly used in the study of the energy absorption performance of various aluminum foams [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the energy absorption performance of the aluminum foam, they also proposed the energy absorption efficiency and the ideal energy absorption efficiency. The energy absorption efficiency is broadly used in the study of the energy absorption performance of various aluminum foams [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results reveal that it is possible to produce aluminum metal foam without a stabilizing agent with coequal physical and mechanical properties. D. Yang et al [12] prepared ex-situ aluminum cellular structurefilled tubes. The samples were tested for quasi-static compression and energy absorption behavior, and it was reported that the filling ratio and positioning of the cellular structure inside the tube play a crucial role in tailoring the foam's compression and energy absorption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some effective structures have been proposed and designed to increase the specific strength and energy absorption of lattice structures and foam structures [24][25][26][27]. Metallic and polymeric foams are used as filling material to improve the mechanical performance of sandwich structures with lattice cores and have proved to be effective [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%